DEPERSONALIZATION/DEREALIZATION DISORDER: JENNIFER’S RECOVERY STORY - Jones, Jennifer L.; Abraham, Samuel P. (International Journal of Research -GRANTHAALAYAH, 2019)
Depersonalization/derealization disorder is not commonly known. A nursing student experienced depersonalization/derealization attack just as she was taking her pharmacology examination at the end of the first year of nursing school. She was brought up in a supportive family. She reports no history of abuse or substance use. She succeeded well in high school and have had no serious panic episodes throughout her childhood and teen years. Jennifer tells the story of how on April 24th, 2017 her life changed.